9514 1404 393
Answer:
- Equivalent
- Not Equivalent
- Equivalent
- Not Equivalent
Explanation:
The applicable rules of exponents are ...
(a^b)(a^c) = a^(b+c)
(a^b)^c = a^(bc)
__
The left-side expressions (all the same) can be simplified to ...
(7^(1/5))·(49^(7/5)) = (7^(1/5))·((7^2)^(7/5))
= (7^(1/5))·(7^(14/5)) . . . . . . matches 3rd right-side expression
= 7^(1/5 +14/5) = 7^(15/5) = 7^3
= 343 . . . . . . . . . . . . . . . . . . matches 1st right-side expression
__
49 is obviously not equivalent to 343.
49^(2/10) is obviously not equivalent to 49^(7/5).